Dynamic tracks of industrial carbon emissions from energy consumption in Guangdong, China - Chen, Lei; Xu, Linyu (Journal of Environmental Accounting and Management, 2026)
Regional diversity of economic situation and production levels lead to significant differences of regional carbon emissions between cities, gravity center can dynamically and clearly reflect the trajectory changes of regional economic development and carbon emissions. In this paper, gravity center is used to depict the dynamic changes of industrial GDP and indus-trial carbon emissions in Guangdong, China from the past decade. By analyzing the center movements, the industrial centers and carbon center had similar tracks in west direction. Energy consumption by Western Guangdong increased rapidly during the study period, with the gravity center of carbon emissions moving in southwest direction. The method would help to reveal the effects of transfer on industrial carbon emissions, and simulate the further procedures of regional industrial transfer.